Response of Convective Boundary Layer and Shallow Cumulus to Soil Moisture Heterogeneity: A Large‐Eddy Simulation Study. (12th December 2019) - Han, Cunbo; Brdar, Slavko; Kollet, Stefan
Abstract: In this study, the impact of varying soil moisture heterogeneity (spatial variance and structure) on the development of the convective boundary layer and shallow cumulus clouds was investigated. Applying soil moisture heterogeneity generated via spatially correlated Gaussian random fields based on a power law model and idealized atmospheric vertical profiles as initial conditions, three sets of large‐eddy simulations provide insight in the influence of soil moisture heterogeneity on the ensuing growth of the convective boundary layer and development of shallow cumulus clouds. A sensitivity on the strong, weak, and unstructured soil moisture heterogeneity is investigated. The simulation results show that domain‐averaged land surface sensible heat and latent heat flux change strongly with changing soil moisture variance because of the interactions between surface heterogeneity and induced circulations, while domain means of soil moisture are identical. Vertical profiles of boundary layer characteristics are strongly influenced by the surface energy partitioning and induced circulations, especially the profiles of liquid water and liquid water flux. The amount of liquid water and liquid water flux increases with increasing structure. In addition, the liquid water path is higher in case of strongly‐structured heterogeneity because more available energy is partitioned into latent heat and more intensive updrafts exist. Interestingly, the increase of liquid water path with increasing soil moisture variance only occurs in the strongly structured cases, which suggests that soil moisture variance and structure work conjunctively in the surface energy partitioning and the cloud formation. Plain Language Summary: The land surface is heterogeneous with respect to, for example, land use, plant cover, soil moisture, and topography over a wide range of spatial scales, which strongly influences the atmospheric boundary layer. In this study, the impact of soil moisture heterogeneity on the development of the convective boundary layer and shallow cumulus clouds was investigated. The results from a series of large‐eddy simulations show that soil moisture heterogeneity impacts significantly on the surface energy partitioning, the convection boundary layer development and the cloud formation. Interestingly, the stronger soil moisture heterogeneity, the more available energy is partitioned into latent heat flux and the higher liquid water path in the atmosphere. Key Points: The higher soil moisture variance the more available energy is partitioned into latent heat flux, while the domain‐averaged soil moisture is identical Liquid water path increases, while cloud cover decreases with stronger soil moisture structure and increasing soil moisture variance The impact of shallow cumulus clouds on domain‐averaged surface net radiation is not significant